ChemInform Abstract: Microwave‐Assisted Synthesis of N‐Heterocycles in Medicinal Chemistry. Issue 3 (21st January 2014) - Garella, Davide; Borretto, Emily; Di Stilo, Antonella; Martina, Katia; Cravotto, Giancarlo; Cintas, Pedro
Abstract Review: 103 refs.